Cloning, Expression, and Characterization of cis-Polyprenyl Diphosphate Synthase from the Thermoacidophilic Archaeon Sulfolobus acidocaldarius - Hemmi, Hisashi (American Society for Microbiology, 2001)
cis-polyprenyl diphosphate synthases are involved in the biosynthesis of the glycosyl carrier lipid in most organisms. However, only little is known about this enzyme of archaea. In this report, we isolated the gene of cis-polyprenyl diphosphate synthase from a thermoacidophilic archaeon, Sulfolobus acidocaldarius, and characterized the recombinant enzyme.